Genetic variation in PEAR1, cardiovascular outcomes and effects of aspirin in a healthy elderly population - Lewis, J.P.; Riaz, M.; Xie, S.; Polekhina, G.; Wolfe, R.; Nelson, M.; Tonkin, A.M.; Reid, Christopher; Murray, A.M.; McNeil, J.J.; Shuldiner, A.R.; Lacaze, P. (2020)
This article is protected by copyright. All rights reserved.